2024
DOI: 10.3389/fnut.2024.1305394
|View full text |Cite
|
Sign up to set email alerts
|

Does millet consumption contribute to raising blood hemoglobin levels compared to regular refined staples?: a systematic review and meta-analysis

Seetha Anitha,
Takuji W. Tsusaka,
D. Ian Givens
et al.

Abstract: Millets are recognized for their health and nutritional values, and the United Nations declared 2023 the International Year of Millets. Among the several health and nutritional benefits of millets, their impact on hemoglobin concentration is important since anemia is a major public health issue in many countries. To investigate the effect of millet (including sorghum) consumption on hemoglobin concentration in the blood, a systematic review and meta-analysis were conducted. Thirteen published studies featuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Diet based trials with millet supplementation have shown encouraging results on health and performance. Trials on supplementation of diet with millets have been promising, showing improvement in health and performance including anemia ( 24 ). Regular supplementation of multi-millet health mix (kodo millet, little millet, foxtail millet, finger millet, and wheat with the inclusion of pulses) to primary school children in India showed a positive effect in increasing the anthropometric indices ( 25 ).…”
Section: Nutritional Profile Of Millets and Their Potential As Nutrie...mentioning
confidence: 99%
“…Diet based trials with millet supplementation have shown encouraging results on health and performance. Trials on supplementation of diet with millets have been promising, showing improvement in health and performance including anemia ( 24 ). Regular supplementation of multi-millet health mix (kodo millet, little millet, foxtail millet, finger millet, and wheat with the inclusion of pulses) to primary school children in India showed a positive effect in increasing the anthropometric indices ( 25 ).…”
Section: Nutritional Profile Of Millets and Their Potential As Nutrie...mentioning
confidence: 99%
“…A recent systematic review and meta-analysis [ 66 ] assessed whether millet (pearl, finger, sorghum) consumption contributed to increasing blood haemoglobin compared with refined rice and/or wheat. Twelve papers with thirteen eligible studies were included.…”
Section: Can Millet Consumption Help To Reduce Anaemia?mentioning
confidence: 99%